EFL lecturers’ reflections of AI use in classroom instruction - Silfia, Seva; Jaya, Sinarman (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2025)
AI is increasingly used in language classrooms, yet EFL lecturers’ experiences and reflections remain underexplored. This mixed-methods study examined lecturers’ awareness, classroom practices, pedagogical adaptations, reflective approaches, professional development needs, and expectations regarding AI use. Thirty lecturers from four universities in Bengkulu, Indonesia, were purposively sampled. Data were collected via a validated questionnaire and semi-structured interviews and analysed using SPSS and thematic analysis. Findings showed that 76% of lecturers regularly used AI, with younger lecturers using it more than older ones (p < .05). Most found AI beneficial but expressed concerns about plagiarism and overreliance. The study highlights lecturers’ experiences, reflective practices, and professional development needs for responsible AI integration. Future research should investigate students’ engagement with AI and strategies to ensure sustainable, effective, and ethical use in language classrooms.